Divorced Women Attitudes Towards Remarriage: A Qualitative Approach - Fathima Sahala K (International Journal of Behavioral Sciences, 2026)
The current study aimed to investigate the attitudes of divorced women regarding remarriage and to comprehend the diverse factors that shape their viewpoints. The research population comprised divorced women, and a purposive sampling method was employed to select participants. Data were collected from ten divorced women through semi-structured interviews, allowing for in-depth exploration of personal experiences and viewpoints. A qualitative research design was adopted to capture the complexity of individual attitudes, and thematic analysis was employed to identify key patterns and themes emerging from the data. The study examined multiple dimensions related to remarriage, including emotional readiness, social and family support, personal experiences, societal perceptions, and challenges encountered by divorced women. Findings revealed that attitudes toward remarriage are shaped by a combination of personal, social, and cultural factors. Age, the presence of minor children, and concerns related to intimacy and companionship were identified as significant influences on decision-making. Emotional and financial support systems also played an important role in shaping participants’ willingness to consider remarriage. Family dynamics and prevailing societal norms were found to significantly affect women’s perspectives, either encouraging or discouraging remarriage depending on cultural expectations and family attitudes. Many participants expressed concerns about social acceptance, stigma, and the potential impact of remarriage on their children. Additionally, emotional challenges such as trust issues, fear of repeating past mistakes, and unresolved emotional experiences were highlighted as important considerations affecting readiness for new relationships. Despite these challenges, several participants viewed remarriage as an opportunity for personal growth, companionship, and emotional fulfillment. The findings indicate that divorced women’s attitudes toward remarriage are diverse and influenced by individual life circumstances, past experiences, and support networks. Overall, the study emphasizes the complexity of the decision-making process surrounding remarriage and underscores the importance of understanding personal and social contexts when examining such attitudes.
Keywords: Attitudes toward remarriage; Challenges; Children; divorced women; emotional support; family dynamics; financial support; personal growth; societal perception